MEDIASI HUKUM DAN KEADILAN RESTORATIF: SEBUAH PENDEKATANTERPADU DALAM PENYELESAIAN SENGKETA PERJANJIAN - Rahmawati, Rahmawati; Bulqis, Bulqis (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
ABSTRACT Contractual disputes in Indonesia often lead to protracted conflicts, particularly in business contracts and commercial agreements. Formal litigation tends to be time-consuming, expensive, and has negative socio-economic impacts, creating an urgent need for more effective alternative resolutions. Legal mediation combined with restorative justice principles offers a solution that emphasizes efficiency, fairness, and the restoration of relationships between parties. This phenomenon emphasizes the need for a comprehensive approach and a thorough understanding of mediation and restorative justice as contractual dispute mitigation strategies. This study explores the application of legal mediation integrated with restorative justice principles in resolving contractual disputes, as well as its impact on legal certainty and maintaining relationships between parties. This study also formulates an integrated approach model that accommodates formal law and restorative principles, while analyzing the role of mediators and legal barriers in mediation practice. The results are expected to provide a conceptual basis and policy recommendations for the development of non-litigation dispute resolution mechanisms in Indonesia and to enrich contemporary legal literature. This study uses a normative juridical approach with qualitative methods, focusing on the analysis of legal documents, literature, and regulations related to mediation and restorative justice. This approach integrates legal certainty with restorative justice principles to formulate a comprehensive contractual dispute resolution model while identifying legal gaps and innovations in mediation practices in Indonesia. The novelty of this research demonstrates that legal mediation combined with restorative justice increases the effectiveness of contractual dispute resolution, reduces conflict, and strengthens relationships between parties. This approach produces solutions that are both legally valid and socially just, and reduces the risk of recurrent litigation. The findings emphasize the importance of mediator capacity, regulatory reform, and adjustments to legal procedures to align with restorative justice principles. This research develops an integrated mediation model as a systematic and contextual innovation, offering implementation guidelines, mediator training, and regulatory harmonization. The novelty lies in the integration of legal certainty with restorative justice, opening a new paradigm to strengthen public trust in the legal system and providing a basis for further research in various contractual disputes. Keywords: Legal Mediation, Restorative Justice, Contractual Disputes